Improved Graft Function and Decreased Post-transplantation Urinary Tract Infection after Azithromycin Dosing to Donors: A Pilot Study - Teimoori, Mojtaba; Mokhtari, Gholamreza; Falahatkar , Siavash; Khosravi , Masoud; Momeni Moghaddam, Majid; Taheri , Zahra (Urology Journal, 2025)
Purpose: The rising trend of End-stage Renal Disease (ESRD) patients requiring dialysis or transplantation needs a more therapeutic plan. As the best strategy for ESRD patients, kidney transplantation still needs outcome improvement. Macrolide drugs display antimicrobial and anti-inflammatory properties in chronic disease and intraoperatively and can concentrate in tissues for extended periods. Hence, theoretically, the drug prescription to the donor and accumulation in the kidney can cause graft immunomodulation and improve kidney transplantation outcomes. Methods and Analysis: This double-blinded randomized clinical trial was conducted on 62 eligible kidney donors randomly allocated to the azithromycin or placebo group and treated with a single dose (one gram) one day before surgery. The primary outcome was kidney graft function, and secondary outcomes included rejection rate, urinary tract infections in graft recipients, pain and systemic inflammatory response syndrome in live donors, and complications in donors and recipients. Outcomes were measured at baseline and every day in the first week after transplantation in both live donors and recipients and 30 and 90 days after transplantation. The adverse events were recorded as well. Result: The mean age was 39 (SD, 13) years; 40% were women, and 11.6% were diabetic. Mean creatinine was 6.11 mL/min/1.73m2. Most patients in both arms were male (61.3%) and in early middle age. Hypertension was the most common cause of ESRD. Azithromycin could reduce the rejection rate in the first few days after kidney transplantation. Inflammatory mediators were lower in the azithromycin group, and fewer cases of urinary tract infection were found in the azithromycin group (p < 0.05). Conclusion: Azithromycin reduces adverse outcomes and enhances graft function. It would offer an intervention that is easy to use and economical, lowering post-transplant risks.